2018
DOI: 10.1002/hep.30045
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Hepatocellular Carcinoma Among Liver Transplant Registrants in the Direct Acting Antiviral Era

Abstract: In this large population-based cohort of LT registrants, the incidence of HCC among HCV patients has increased in the DAA era. Competing risks analysis suggests that this may be explained by changes in rates of LT and wait-list mortality in the HCV population during this time. (Hepatology 2018; 00:000-000).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The diagnosis of HCC among UNOS registrants was based on HCC Model for End-Stage Liver Disease (MELD) exception application as described. (22) In brief summary, diagnosis of HCC was based on histological or specific imaging criteria (e.g., arterial phase enhancement, venous washout, peripheral rim enhancement, or growth by 50% or more on serial imaging obtained fewer than 6 months apart). To qualify for MELD exception points, the burden of HCC must be either (1) two or three lesions measuring between 1 and 3 cm or (2) a single lesion measuring between 2 and 5 cm.…”
Section: Hcc Ascertainmentmentioning
confidence: 99%
“…The diagnosis of HCC among UNOS registrants was based on HCC Model for End-Stage Liver Disease (MELD) exception application as described. (22) In brief summary, diagnosis of HCC was based on histological or specific imaging criteria (e.g., arterial phase enhancement, venous washout, peripheral rim enhancement, or growth by 50% or more on serial imaging obtained fewer than 6 months apart). To qualify for MELD exception points, the burden of HCC must be either (1) two or three lesions measuring between 1 and 3 cm or (2) a single lesion measuring between 2 and 5 cm.…”
Section: Hcc Ascertainmentmentioning
confidence: 99%
“…An initial small cohort study by Reig et al[25] suggested an increase in rates of HCC following DAA therapy, however a large meta-analysis subsequently found no difference in HCC occurrence in patients following SVR from DAA vs IFN-based treatment[26]. Kwong et al[27] recently showed that although the incidence of de novo HCC in patients with HCV cirrhosis has increased in the DAA era, these changes may be explained by changes in the rates of liver transplantation among HCV patients and wait list mortality. Increasing age and severity of liver disease likely contributes to a higher incidence of HCC in transplant candidates as well[23,27].…”
Section: High Risk Populationsmentioning
confidence: 99%
“…Kwong et al[27] recently showed that although the incidence of de novo HCC in patients with HCV cirrhosis has increased in the DAA era, these changes may be explained by changes in the rates of liver transplantation among HCV patients and wait list mortality. Increasing age and severity of liver disease likely contributes to a higher incidence of HCC in transplant candidates as well[23,27]. Current guidelines continue to recommend HCC surveillance in patients with cirrhosis even after eradication of HCV with DAA therapy[7].…”
Section: High Risk Populationsmentioning
confidence: 99%
“…Patients with a MELD score of more than 18-20 points should be preferably treated post-transplant. Importantly, despite initial concerns, SVR to IFN-free therapies does neither increase the risk of de novo hepatocellular carcinoma (HCC) development [21] nor recurrence of HCC after local ablative therapies [22].…”
Section: Treatment Of Chronic Hepatitis C (Chc) Before and After Oltmentioning
confidence: 99%